2015
DOI: 10.1186/scrt535
|View full text |Cite
|
Sign up to set email alerts
|

Loss of non-coding RNA expression from the DLK1-DIO3 imprinted locus correlates with reduced neural differentiation potential in human embryonic stem cell lines

Abstract: IntroductionPluripotent stem cells are increasingly used to build therapeutic models, including the transplantation of neural progenitors derived from human embryonic stem cells (hESCs). Recently, long non-coding RNAs (lncRNAs), including delta-like homolog 1 gene and the type III iodothyronine deiodinase gene (DLK1-DIO3) imprinted locus-derived maternally expressed gene 3 (MEG3), were found to be expressed during neural development. The deregulation of these lncRNAs is associated with various neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
200
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(201 citation statements)
references
References 60 publications
1
200
0
Order By: Relevance
“…This set includes almost all lncRNAs that have been demonstrated in literature to play a role in neuronal development, such as MIAT, TUG1, DGCR5, MEG3, and TUNA 263743444546. One lncRNA with validated function during neurogenesis that is notably absent in our candidate list is RMST 35.…”
Section: Discussionmentioning
confidence: 99%
“…This set includes almost all lncRNAs that have been demonstrated in literature to play a role in neuronal development, such as MIAT, TUG1, DGCR5, MEG3, and TUNA 263743444546. One lncRNA with validated function during neurogenesis that is notably absent in our candidate list is RMST 35.…”
Section: Discussionmentioning
confidence: 99%
“…After the cells were cultured for 24 hours, the migration of astrocytes was recorded with a time-lapse microscope (Zeiss Axio Observer microscope) placed in a plastic incubator with 5% CO 2 at 37°C. 69, 70 Sterile conditions were maintained throughout. The time-lapse image recording was performed to record cell migration using ZEN 2011 imaging microscope software.…”
Section: Methodsmentioning
confidence: 99%
“…DNMT3L mutations have been associated with schizophrenia, subtelomeric hypomethylation, lower intelligence and ovarian endometriosis (El-Maarri et al 2009, Haggarty et al 2010, Borghese et al 2012, Saradalekshmi et al 2014. Recent studies have shown that the loss of Dnmt3l expression correlates with failed TE silencing and defective genomic imprinting at the Dlk1-Dio3 locus in induced pluripotent stem cells (iPSCs) (Stadtfeld et al 2012, Tang et al 2012, which might correlate with reduced neural lineage differentiation potential (Stadtfeld et al 2012, Mo et al 2015. Dnmt3l-mutant iPSCs are therefore not suitable for biomedical research.…”
Section: Discussionmentioning
confidence: 99%